(untitled) (MMIT Proceedings, 2024)
the article discusses current trends and challenges in education management in Uzbekistan within the context of globalization. It analyzes changes taking place in Uzbekistan’s education system in recent years, focusing on the introduction of innovations, development of information and communication technologies, and active learning methods. The article also explores the issue of quality assurance in education, assessment of student outcomes, and adaptation of the education system to international standards.